1987
DOI: 10.1037/0022-006x.55.2.139
|View full text |Cite
|
Sign up to set email alerts
|

The role of health beliefs in the regimen adherence and metabolic control of adolescents and adults with diabetes mellitus.

Abstract: The current study examined the role of health beliefs in diabetic regimen adherence and metabolic control. The subjects were 143 insulin-dependent diabetic outpatients, including 54 from a university juvenile diabetes care clinic with a mean age of 18 and 89 from a private practice clinic with a mean age of 37. Subject age and knowledge about diabetes were statistically controlled for in the multiple regression equations used to analyze the data. Overall, health beliefs accounted for a statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
81
3
6

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(97 citation statements)
references
References 15 publications
7
81
3
6
Order By: Relevance
“…A number of studies demonstrated that both personal health beliefs and self-efficacy predicted self-care across a wide range of behaviors in both adolescents and adults (Brownlee-Duffeck et al, 1987;McCaul, Glasgow, & Schafer, 1987). A recent meta-analysis concluded that research findings have continued to show that these cognitive and attitudinal processes have direct effects on self-management and, thus, significant indirect effects on clinical outcome (Robiner & Keel, 1997).…”
Section: Individual Variablesmentioning
confidence: 99%
“…A number of studies demonstrated that both personal health beliefs and self-efficacy predicted self-care across a wide range of behaviors in both adolescents and adults (Brownlee-Duffeck et al, 1987;McCaul, Glasgow, & Schafer, 1987). A recent meta-analysis concluded that research findings have continued to show that these cognitive and attitudinal processes have direct effects on self-management and, thus, significant indirect effects on clinical outcome (Robiner & Keel, 1997).…”
Section: Individual Variablesmentioning
confidence: 99%
“…Previous studies sometimes calculated a total score for self-management [13,14], but researchers now agree that different aspects of self-management should be assessed separately because of its multidimensional nature [15][16][17]. A variety of questionnaires have been developed, most of which focus on the frequency with which people perform their selfmanagement tasks in a variety of areas.…”
Section: Introductionmentioning
confidence: 99%
“…Differentiating between long-and short-term beliefs may also be important in understanding the conflicting results for threat expectancies in previous work on adolescents with diabetes (18,20,25). Whether predicting anxiety, depression, or dietary self-management in adolescents, it was the short-term effects of the illness and its treatment (perceived impact of diabetes and effectiveness of treatment to control diabetes) that were important (19).…”
Section: Adolescent Personal Modelsmentioning
confidence: 99%